2022
DOI: 10.1088/2058-6272/ac41bd
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anomalous transport based on radial fractional diffusion equation

Abstract: The anomalous transport in magnetically confined plasmas is investigated by the radial fractional transport equations. It is shown that for fractional transport models, hollow density profiles are formed and uphill transports can be observed regardless of whether the fractional diffusion coefficients (FDCs) are radially dependent or not. When a radially dependent FDC Dα(r)<1 is imposed, compared with the case under Dα(r)=1.0, it is observed that the position of the peak of the density profile is closer to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…It should be pointed out that non-local effects are also important to transport in Markovian processes, as investigated in Refs. [35][36][37][38]. It would be interesting to consider both non-local and memory effects at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that non-local effects are also important to transport in Markovian processes, as investigated in Refs. [35][36][37][38]. It would be interesting to consider both non-local and memory effects at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…In early works, hollow temperature profiles were observed in steady states under off-axis heating, [34] and theories based on nonlocal transport by utilizing the spatial fractional transport equation in Markovian processes were developed. [35][36][37][38] In order to investigate memory effects on the formation of hollow temperature profiles under off-axis heating processes, we assume the heating source to be of the form H add = H e e −(r−r 0 ) 2 /a 2 , where r 0 = 0.75, a = 0.05, and H e is a constant, such that 2π 1 0…”
Section: Applications To Magnetically Confined Plasmasmentioning
confidence: 99%
“…Kaibang Wu et al analyzed anomalous transport based on the radial fractional diffusion equation. If the particles sit in strong turbulence with large fluctuation amplitude, the particles are trapped, and the average of their square of displacement is not proportional to time anymore, which can be described by the radial fractional transport model [26]. It is shown that for fractional transport models, hollow density profiles are formed and uphill transports can be observed regardless of whether the fractional diffusion coefficients (FDCs) are radially dependent or not.…”
Section: Micro-turbulence and Transportmentioning
confidence: 99%